Fancy Nancy's favorite fancy words : from accessories to zany - O'Connor, Jane (O'Connor, Jane. Fancy Nancy., 2008)
Fancy Nancy provides one or more of her favorite fancy words for each letter of the alphabet, defines them, and uses some in sentences that show what they mean to her, such as that she yearns--wants really badly--to visit Paris someday.